FETAL COMPLICATIONS IN PREGNANT WOMEN WITH MULTIPLE PREGNANCY - Khattak, Saima; Bilal, Muhammad; Khan, Yaseen (Khyber Journal of Medical Sciences, 2022)
OBJECTIVE: To determine the fetal complications associated with multiple pregnancy in second and third trimester of pregnancy. METHODOLOGY: This descriptive study was carried out in the obstetrics and Gynaecology department at Postgraduate Medical Institute Lady Reading Hospital Peshawar. Duration of the study was 1 year from January 2012 to December 2012. All patients with twin gestations, triplets and high order multiplets visiting obstetrics and Gynaecology unit of the institute and who were admitted in ward and their fetal with complications were included in the study. Results: Sixty patients with multiple gestations were included in the study. In 28 patients (46.7%) cephalic/ cephalic was the most common presentation. Among the 126 total fetuses in this study, 64 fetuses (50.8%) had low birth weight. 51 fetuses (40.4%) were premature, overall fetal loss was 16 (12.6%), 37 fetuses (29.3%) were admitted in nursery. 77 fetuses (61.1%) had apgar score of more than 7 at 5 minutes, while rest of the babies had Apgar score of less than that. Among fetal complications prematurity was recorded in 51 (40.4%) cases, admission in nursery in 37 (29.3%), IUGR in 20 (16.7%), still birth in 16 (12.6%), fetal distress in 2 (1.6%), congenital anomalies in 2 (1.6%) and demise of one fetal in 01 (0.7%) cases. CONCLUSION: Multiple gestations are considered as pregnancies at high risk, which may be convoluted by prematurity, admission in nursery, low birth weight infants, intrauterine growth retardation, neonatal morbidity and mortality as showed in the results of our study